Ultrasonically sprayed cobalt oxide thin films: Enhancing of some physical properties by nickel doping - Kus, Esra; Kucukarslan, Ayse; Demirselcuk, Barbaros; Sarıca, Emrah; Akyuz, Idris; Bilgin, Vildan (Elsevier B.V., 2021)
In this study, the effect of Ni doping (3, 6, 9 at%) on structural, optical, electrical and magnetic properties of Co3O4 films was reported. Films were grown at 300 ± 5 °C substrate temperature via ultrasonic spray pyrolysis (USP) technique. The structural analyses showed that undoped and Ni (3%) doped films exhibit an amorphous structure. Ni doping at higher ratios caused the films to have improved crystallinity. Optical band gap values the films were found to be between 2.03 and 2.08 eV with an additional sub-band corresponding to energies varying between 1.35 and 1.46 eV. The electrical conductivity values of the films increased significantly depending on the Ni doping. The hysteresis curves of the films showed that the films have weak ferromagnetic properties. Ni doping significantly improved the structural and electrical properties of Co3O4 films making them suitable materials for technological applications.
Keywords: Cobalt Nickel oxide; Magnetic materials; Optical and electrical properties; Spray pyrolysis; Structural